2021
DOI: 10.1515/jcim-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jyoti-Trataka on intraocular pressure, autonomic control, and blood glucose in diabetic patients with high-tension primary open-angle glaucoma: a randomized-controlled trial

Abstract: Objectives Yoga is used as a complementary therapy to control the symptomatic and complicated consequences of type 2 diabetes mellitus (T2DM) but the effect of Jyoti-Trataka yoga (gazing steadily at a 4-feet away-fixed candle flame) on the intraocular pressure (IOP), autonomic control, and fasting blood glucose (FBG) in T2DM patients with high-tension primary open-angle glaucoma (POAG) was not previously investigated. This study aimed to search the effect of Jyoti-Trataka on IOP, systolic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The trabecular mesh tissue of the eye is unlocked by this stretch, allowing the aqueous humour to flow freely. Long-term drainage and/or outflow of aqueous humour in response to trataka may help to lower HTPOAG's elevated IOP [13].…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…The trabecular mesh tissue of the eye is unlocked by this stretch, allowing the aqueous humour to flow freely. Long-term drainage and/or outflow of aqueous humour in response to trataka may help to lower HTPOAG's elevated IOP [13].…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Yoga combines both aspects of meditation as well as isometric exercises and has become a popular practice around the world. While relaxing yoga interventions can help to reduce IOP [6,7], other studies have reported increased IOP values during and following common yoga positions in both healthy and glaucoma individuals [8,9]. Therefore, practicing yoga could be seen as a potential risk factor for the development or progression of glaucomatous optic disc damage.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years interest has been rekindled in yoga and the eye, especially yoga and intraocular pressure. 7,[10][11][12][13][14] Various yogic breathing techniques have been shown to alter the brain hemisphere activity, and influence the autonomic nervous system. 15 Right nostril breathing is thought to increase the sympathetic activity and left nostril breathing brings about dominance of parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%